1994
DOI: 10.1021/jm00048a006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-in-the-Ring Pyranoses and Furanoses: Structural Basis of Inhibition of Mammalian Glycosidases

Abstract: Seven pyranoses and three furanoses with a nitrogen in the ring were prepared by chemical synthesis, microbial conversion, and isolation from plants to investigate the contribution of epimerization, deoxygenation, and conformation to the potency of inhibition and specificity of mammalian glycosidases. The seven pyranoses are 1-deoxynojirimycin (1), the D-manno (2), D-allo (3), and D-galacto (4) isomers of 1, fagomine (1,2-dideoxynojirimycin, 5), and the D-allo (6) and D-galacto (7) isomers of 5, while the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 160 publications
(95 citation statements)
references
References 28 publications
5
89
1
Order By: Relevance
“…They found that results with the five-membered-ring compound, 1,4-dideoxy-l,4-imino-D-arabinitol, superimpose well on the binding model on the basis of the mannosyl cation geometry. 1,4-Dideoxy-1,4-imino-D-arabinitol also superimposes well on the glucosyl cation, since it has two ring hydroxyl groups lying in the same region of space as C3 and C4 of a putative glucosyl cation, with the hydroxymethyl group also being topographically equivalent (Asano et al, 1994). 1,4-Dideoxy-l ,4-imino-D-arabinitoI is a good inhibitor of endoplasmic reticulum a-glucosidase I1 (K, = 9.7 pM) as well as Golgi a-mannosidase I1 (K, = 35 pM; Asano et al, 1994).…”
Section: Inhibition Of Pig Kidney Trehalase By Sugar Analogsmentioning
confidence: 91%
See 2 more Smart Citations
“…They found that results with the five-membered-ring compound, 1,4-dideoxy-l,4-imino-D-arabinitol, superimpose well on the binding model on the basis of the mannosyl cation geometry. 1,4-Dideoxy-1,4-imino-D-arabinitol also superimposes well on the glucosyl cation, since it has two ring hydroxyl groups lying in the same region of space as C3 and C4 of a putative glucosyl cation, with the hydroxymethyl group also being topographically equivalent (Asano et al, 1994). 1,4-Dideoxy-l ,4-imino-D-arabinitoI is a good inhibitor of endoplasmic reticulum a-glucosidase I1 (K, = 9.7 pM) as well as Golgi a-mannosidase I1 (K, = 35 pM; Asano et al, 1994).…”
Section: Inhibition Of Pig Kidney Trehalase By Sugar Analogsmentioning
confidence: 91%
“…1,4-Dideoxy-1,4-imino-D-arabinitol also superimposes well on the glucosyl cation, since it has two ring hydroxyl groups lying in the same region of space as C3 and C4 of a putative glucosyl cation, with the hydroxymethyl group also being topographically equivalent (Asano et al, 1994). 1,4-Dideoxy-l ,4-imino-D-arabinitoI is a good inhibitor of endoplasmic reticulum a-glucosidase I1 (K, = 9.7 pM) as well as Golgi a-mannosidase I1 (K, = 35 pM; Asano et al, 1994). In this work, it more potently inhibited pig kidney trehalase than did I-deoxynojirimycin, with a K, value of 3.6 pM.…”
Section: Inhibition Of Pig Kidney Trehalase By Sugar Analogsmentioning
confidence: 91%
See 1 more Smart Citation
“…All these compounds inhibited a-l-fucosidases in a competitive manner. 2R,5R-Bis(hydroxymethyl)-3R,4R-Dihydroxypyrrolidine (DMDP, 2,5-dihydroxy-2,5-imino-d-mannitol), which was first isolated from the leaves of the legume Derris elliptica [14] and is now being reported in many disparate species of plants and microorganisms [15], has been shown to be a potent inhibitor of mammalian b-galactosidases [16]. The 6-deoxy derivative (6) of DMDP has been isolated from the seeds of A. pynaertii and reported to be a moderate inhibitor of Aspergillus niger b-mannosidase, with an IC 50 value of 380 mm [5].…”
Section: Inhibition Of A-l-fucosidase By Sugar-mimic Alkaloidsmentioning
confidence: 99%
“…Resembling D-glucose in structure as well as in the transition state of glucosidase-catalyzed reactions, DNJ is able to inhibit α-glucosidase in a competitive manner [9,10]. Given that DNJ showed good inhibitory activity against α-glucosidase [11], a number of DNJ derivatives have been synthesized in order to achieve significant potency of suppressing post-prandial elevation of the glucose level in blood. Successful results were first obtained with miglitol and emiglitate.…”
Section: Introductionmentioning
confidence: 99%